Emerging as early childhood teacher: critical challenges - Lino, Dalila Maria Brito Cunha (2015)
This study aims to understand the experiences of beginning early childhood teachers as they transition roles from student to first-year teacher. Research has shown that are major areas of concern for novice teachers: relationships, knowledge of the curriculum, evaluation and grading, issues in autonomy and control, and workload and time management. Research also has identified a troubling support gap for new teachers during their first critical years in the job. Fifteen early childhood teachers in their first year of teaching were interviewed for this case study research. data were submitted to content analyse process which allowed identifying major themes, namely: initial expectations and feelings; problems and difficulties; types of support; achievements; critical moments; perceived changes. The data highlight the need to reflect on early childhood teacher education. The emphasis should be on how to help teachers to construct professional understanding from field-based experiences.